Modifiable Survival Factors of Out-of-Hospital Cardiac Arrest among Global Population: Systematic Review and Meta-Analysis - Jeremy Rafael Tandaju; Kareen Tayuwijaya (The Indonesian Heart Association, 2020)
Out-of-hospital cardiac arrest (OHCA) is the most common type of cardiac arrest and causing much mortality and burden even preventive measure has been made. Therefore, we conducted study to reduce OHCA morbidity and mortality by finding modifiable survival factors in-order to interfere them. We did systematic review of large cohort studies (n>100,000) on general population from four databases, then filtered 3,560 studies into 9 studies and appraised them using Newcastle-Ottawa scale for quality and Cochrane risk-of-bias before being synthesized. Among 486,012 subjects, we found out that age and shockable rhythm is unmodifiable but could be helped with lifestyle. Modifiable factors are grouped into two: bystander response including public location (OR=1.24; CI 95%=1.16–1.32), bystander witness (OR=1.45; CI 95%=1.36–1.56), bystander CPR (OR=1.45; CI 95%=1.36–1.56); and emergency service delivery including paramedic response <10 minutes (OR=1.55; CI 95%=1.41–1.70), ambulance physician (OR=1.52; CI 95%=1.37–1.68). Having OHCA in public means bigger chance of being resuscitated. However, resuscitation by uneducated bystander shown harmful thus public education was needed. Emergency services were considered important to arrive with competent workers, especially physicians who was trained on defibrillator usage and management regiment. Therefore, increasing public awareness, provide more ambulance and district health center facility, and training of health care workers are essential. In conclusion, management of OHCA involved multidisciplinary action throughout the nation to increase outcome of OHCA and lessen the burden. More area-specified and factor-specified studies should be conducted to improve applicability.